1999
DOI: 10.1002/(sici)1097-4636(199904)45:1<20::aid-jbm3>3.0.co;2-6
|View full text |Cite
|
Sign up to set email alerts
|

Bioadhesion of gelatin films crosslinked with glutaraldehyde

Abstract: The present study was carried out in an attempt to make a gelatin film strongly bioadhesive by introducing free dangling aldehyde groups. When gelatin films were treated with 0.5M of glutaraldehyde (GA) solution at 60 degrees C, free aldehyde groups (up to 150 micromol/g) were introduced in the film. The bonding strength of GA-crosslinked gelatin films (GA gelatin films) with biological tissue was assessed using porcine skins. It was found that bonding strength increased with increasing aldehyde content in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
93
0
3

Year Published

2003
2003
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 159 publications
(96 citation statements)
references
References 10 publications
0
93
0
3
Order By: Relevance
“…The tensile strength of more than 2.0 mg cm −2 chitosan membranes showed higher than 3.0 N indicating to have a potential to use for a surgical tape. 10 Based on the results, we used 2.0 mg cm −2 chitosan membrane for further experiments.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The tensile strength of more than 2.0 mg cm −2 chitosan membranes showed higher than 3.0 N indicating to have a potential to use for a surgical tape. 10 Based on the results, we used 2.0 mg cm −2 chitosan membrane for further experiments.…”
Section: Resultsmentioning
confidence: 99%
“…The DNA-chitosan bilayer membranes were suggested to have enough tensile strength as a surgical tape. 10 Next, we observed the surface of the DNA-chitosan membranes using a SEM (Figure 4). The UV-irradiated DNA membrane showed fiber-like surface structure ( Figure 4 Va and Vb).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…14 Furthermore, Matsuda et al have reported that the aldehyde groups introduced in the cross-linked biopolymers can be quenched with glycine to reduce the cytotoxicity of chemical compounds. 15 Our previous study has also shown that human retinal pigment epithelial cell viability is significantly increased for GTA cross-linked gelatin samples with glycine treatment compared with their counterparts without glycine treatment. 16 Therefore, in this study, the AM materials following GTA cross-linking are placed in glycine aqueous solution for the capping of residual aldehyde groups.…”
Section: Introductionmentioning
confidence: 91%
“…Reverse transcription of the extracted RNA (1 µg) was performed using ImProm-II™ (Promega) and Oligo(dT) 15 primers (Promega). The primers used to amplify the human interleukin 6 (IL-6) complementary DNA (cDNA) were 5′-CCACTCACCTCT-TCAGAACGAA-3′ (sense) and 5′-GGCAAGTCTC-CTCATTGAATCC-3′ (antisense).…”
Section: Proinflammatory Gene Expression Analysesmentioning
confidence: 99%